Effects of pre-pregnancy maternal body mass index on gestational diabetes mellitus - Shirley Muller, Priya; Nirmala, M (International Journal of Engineering and Technology, 2018)
The prevalence of both obesity and Gestational Diabetes Mellitus (GDM) is increasing worldwide. Overweight and obesity are abnormal or excessive fat accumulation that presents a risk to health. The presence of obesity has, in particular, a significant impact on both maternal and fetal complications associated with GDM. These complications can be addressed, at least in part, by good glycaemic control during pregnancy. The objective of the study is to classify GDM and non-GDM patients based on pre-pregnancy maternal Body Mass Index (BMI) and to assess and quantify the risk for GDM according to BMI.